A pathogenic nonsense mutation (c.1522C>T) of the MYBPC3 gene is implicated with hypertrophic cardiomyopathy - Erru Ni; Tao Wang; Xuan Zhang; Huabin Xie (ESC Heart Failure, 2023)
Abstract Hypertrophic cardiomyopathy (HCM), a genetically and clinically heterogeneous cardiomyopathy, is commonly caused by mutations in the MYBPC3 gene or other various sarcomeric genes. HCM patients carrying sarcomeric gene mutations may experience an asymptomatic period at early stage but still possess an escalating risk of developing adverse cardiac events including sudden cardiac death. It is crucial to determine the phenotypic and pathogenic effects of mutations in sarcomeric genes. In this study, a 65‐year‐old male was admitted with a history of chest pain, dyspnoea, and syncope and with a family history of HCM and sudden cardiac death. On admission, electrocardiogram indicated atrial fibrillation and myocardial infarction. Transthoracic echocardiography revealed left ventricular concentric hypertrophy and systolic dysfunction (48%), which were ascertained by cardiovascular magnetic resonance. With late gadolinium‐enhancement imaging, cardiovascular magnetic resonance found myocardial fibrosis on left ventricular wall. The exercise stress echocardiography test showed non‐obstructive myocardial changes. Whole‐exome sequencing analysis identified a MYBPC3 gene heterozygous nonsense variant (c.1522C>T) in the patient and one of his healthy grandnieces (18‐year‐old). The patient was diagnosed with non‐obstructive HCM, heart failure, atrial fibrillation, and so on. Medications, ICD implantation, and catheter ablation were chosen to maintain heart function. Our study provides the clinical evidence regarding the HCM pathogenicity of MYBPC3 c.1522C>T variant and highlights the significance of family genetic testing in the diagnosis and management of HCM.